A fly in a tube: Macroevolutionary expectations for integrated phenotypes. (1st December 2018) - Felice, Ryan N.; Randau, Marcela; Goswami, Anjali
Abstract: Phenotypic integration and modularity are ubiquitous features of complex organisms, describing the magnitude and pattern of relationships among biological traits. A key prediction is that these relationships, reflecting genetic, developmental, and functional interactions, shape evolutionary processes by governing evolvability and constraint. Over the last 60 years, a rich literature of research has quantified patterns of integration and modularity across a variety of clades and systems. Only recently has it become possible to contextualize these findings in a phylogenetic framework to understand how trait integration interacts with evolutionary tempo and mode. Here, we review the state of macroevolutionary studies of integration and modularity, synthesizing empirical and theoretical work into a conceptual framework for predicting the effects of integration on evolutionary rate and disparity: a fly in a tube. While magnitude of integration is expected to influence the potential for phenotypic variation to be produced and maintained, thus defining the shape and size of a tube in morphospace, evolutionary rate, or the speed at which a fly moves around the tube, is not necessarily controlled by trait interactions. Finally, we demonstrate this reduced disparity relative to the Brownian expectation for a given rate of evolution with an empirical example: the avian cranium.